Demonstration of extracellular peptidylarginine deiminase (PAD) activity in synovial fluid of patients with rheumatoid arthritis using a novel assay for citrullination of fibrinogen - Damgaard, Dres (Arthritis Res Ther, 2014)
INTRODUCTION: Members of the peptidylarginine deiminase (PAD) family catalyse the posttranslational conversion of peptidylarginine to peptidylcitrulline. Citrullination of proteins is well described in rheumatoid arthritis (RA), and hypercitrullination of proteins may be related to inflammation in general. PAD activity has been demonstrated in various cell lysates, but so far not in synovial fluid. We aimed to develop an assay for detection of PAD activity, if any, in synovial fluid from RA patients. METHODS: An enzyme-linked immunosorbent assay using human fibrinogen as the immobilized substrate for citrullination and anti-citrullinated fibrinogen antibody as the detecting agent were used for measurement of PAD activity in synovial fluid samples from five RA patients. The concentrations of PAD2 and calcium were also determined. RESULTS: Approximately 150 times lower levels of recombinant human PAD2 (rhPAD2) than of rhPAD4 were required for citrullination of fibrinogen. PAD activity was detected in four of five synovial fluid samples from RA patients and correlated with PAD2 concentrations in the samples (r = 0.98, P = 0.003). The calcium requirement for half-maximal activities of PAD2 and PAD4 were found in a range from 0.35 to 1.85 mM, and synovial fluid was found to contain sufficient calcium levels for the citrullination process to occur. CONCLUSIONS: We present an assay with high specificity for PAD2 activity and show that citrullination of fibrinogen can occur in cell-free synovial fluid from RA patients.